Psikoedukasi Self Managament untuk Menurunkan Adiksi Smartphone pada Remaja - Alya Dwi Anggraeni; Djudiyah Djudiyah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
Smartphone addiction refers to excessive smartphone use that can have physical and psychological impacts. The purpose of this study was to provide psychoeducation to increase knowledge about self-management in an effort to reduce smartphone addiction. This study used a pre-experimental research design with a one-group pretest-posttest design on 32 students. Data collection used the Smartphone Addiction Scale-Short Version questionnaire and additional questionnaires developed by the researcher. The results of the paired sample t-test showed an increase in scores after the psychoeducational intervention (p < 0.05). These findings indicate that psychoeducation can be used as an effective approach to preventing and reducing smartphone addiction in adolescents. These findings can provide new insights into the importance of preventing smartphone addiction through psychological and educational approaches that can be applied in the context of adolescent education and health. This study makes an important contribution to the prevention and management of smartphone addiction, with implications for the development of psychoeducational programs that can be implemented in educational and health settings to support adolescent well-being.